Forensic engineering the investigation of failures : proceedings of the Second International Conference on Forensic Engineering organized by the Institution of Civil Engineers and held in London, UK, on 12-13 November 2001 - Neale, B. S. (Thomas Telford, 2001)
Forensic engineering encompasses any engineering discipline that has the potential to be used for the technical investigation of failures. This volume presents papers from leading experts on how to learn from failures of constructed environments (from serviceability to catastophic), and on the implications for construction professionals.